A machine learning approach to integrate big data for precision medicine in acute myeloid leukemia - Su-In Lee (Nature Portfolio, 2018)
Identification of markers of drug response is essential for precision therapy. Here the authors introduce an algorithm that uses prior information about each gene’s importance in AML to identify the most predictive gene-drug associations from transcriptome and drug response data from 30 AML samples.